The Effects Of Geophysical Anomalies On Biology - Giannoulopoulou, Lydia (Journal of Scientific Exploration, 2018)
The effect of location and its geophysical properties on biology has been known since ancient times. This paper makes an attempt to define geophysical anomalies and analyze the various parameters that constitute them. Furthermore, the mechanisms through which these anomalies interact with human biology, flora and fauna are analyzed.